Perkembangan Bahasa Anak Umur 0-3 Tahun dalam Lingkungan Keluarga - Ni Luh Nanik Puspadi; Sukraningsih Gusti Ayu Gede; NI Made Wina Kariasih (Wacana Saraswati Majalah Ilmiah Tentang Bahasa Sastra Dan Pembelajarannya, 2022)
The purpose of this study is to determine the use of Indonesian for children aged 0-3 years in terms of phonological development and the effect of using Indonesian in pronouncing vocabulary and simple sentences. The subject was 2 years 3 months baby named Made Hanindya Adhisti. The data were obtained by using the techniques of observation and interviews then analyzed qualitatively. The results of this study showed that the pronunciation of the language spoken by Hanin at the age of 0-2 years 3 months was pronouncing the words ma..ma.-[ma] [ma], and pa..pa..- [pa ] [pa] and pronouncing other words even though the pronunciation is still not correct, such as the words ajus – [ajus], seali – [sǝali], tatak – [tata?], inga – [[iŋa], ata – [ata], aki – [aki], eyut – [eyut], anum – [anum], ambin – [ambin], acing – [aciŋ], seaka – [sǝaka], uah – [uah], ciaya – [ ciaya], Itus – [itus], kanguyu – [kaŋuyu], aya [aya] these words undergo omission and replacement of phonemes that should be good – [good], once – [skali], brother – [kaka?], ear – [teliŋa], eyes – [eyes], legs – [legs], stomach – [stomach], drink – [drink], take – [take], cat – [kuciŋ], watermelon – [sǝmaŋka], fruit – [ fruit], w olf – [wolf], mouse – [rat], kangaroo - [kaŋguru], crocodile – [crocodile]. This child's language development is influenced by environmental factors, especially, the family applying motherese, recasting, echoing, and expanding.